Beyond the River and the Bay : Some Observations on the State of the Canadian Northwest in 1811 with a View to Providing the Intending Settler with an Intimate Knowledge of That Country - Ross, Eric (Book collections on Project MUSE., 1970)
Based on an imaginary long-lost manuscript by Ian Alexander Bell Robertson invented by the author in order to integrate remarks by contemporary observers into the text. Gives a picture of the Northwest as it was immediately prior to the first white settlement and is based on sources that would have been available to the writer at that time.